Polarization-independent gain in mid-infrared interband cascade lasers - K. Ryczko; G. Sęk (AIP Advances, 2016)
We have calculated the gain function of a type-II W-design AlSb/InAs/GaAsSb/InAs/AlSb quantum wells to be used in an active region of interband cascade lasers, for two linear polarizations of in-plane propagating light: transverse-electric and transverse-magnetic. The effect of external electric field, imitating the conditions in a working device, has also been taken into account. We have proposed an active region design suitable for practical realization of mid-infrared lasing devices with controllable polarization properties. We have also demonstrated a way to achieve polarization-independent gain in mid-infrared emitters, which has not been reported so far.